A COMPARATIVE â€“ CONTRASTIVE INTEGRATION BETWEEN GREENCLOUD AND DYNAMIC DATA CENTER POWER MANAGEMENT (DDCPM) - Alrahamneh, Bader Abdelhafez (European Scientific Journal, ESJ, 2013)
Power saving stands as a core challenge among data center operators in the middle of the increasing cost of energy and cooling. Itâ€™s important to firstly examine the brief definition of each side of the coin in this paper, which handles two approaches in tow papers bring out new approaches to deal with power consumption. The first in (Liu et al., 2009) is titled GreenCloud: A New Architecture for Green Data Center and the second is Dynamic Data Center Power Management: Trends, Issues, and Solutions in (Filani et al., 2008). In (Liu et al., 2009) GreenCloud is basically a new architecture (structure) for Green (online) data center, whereas in (Filani et al., 2008) the so-called DDCPM signifies a wise approach for boosting power allocation inside a certain â€œpower envelopeâ€ and raise server density in data centers. On the other hand, we hereby aims to attach the concept of Virtual Machine (VM) technology in (Liu et al., 2009) to GreenCloud, and the concept of Policy Manager in (Filani et al., 2008) to the said DDCPM term. Some more relevant topics and terms would be presented as well.